1999
DOI: 10.1159/000052863
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine Regulation of Matrix Metalloproteinase Expression in the Normal Human Endometrium

Abstract: Endometrial expression of matrix metalloproteinase (MMP)-3, MMP-7 and MMP-11 occurs during menstrual breakdown and subsequent estrogen-mediated growth, but not during the secretory phase. These enzymes are suppressed by progesterone treatment. Paracrine factors, including transforming growth factor-β (TGF-β) and retinoic acid, are also critical for MMP regulation in the endometrium. In contrast, inflammatory cytokines such as interleukin-1α may block or interfere with steroid-mediated MMP regulation at ectopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 40 publications
(65 reference statements)
2
64
0
Order By: Relevance
“…Matrix metalloproteinases are important enzymes within the stroma that play a major role in the degradation of most components of the extracellular matrix during the menstrual phase (Osteen et al 1999). The pattern of expression of endometrial metalloproteinases during the menstrual cycle in macaques is similar to that reported for women.…”
Section: Noncellular Componentsmentioning
confidence: 55%
“…Matrix metalloproteinases are important enzymes within the stroma that play a major role in the degradation of most components of the extracellular matrix during the menstrual phase (Osteen et al 1999). The pattern of expression of endometrial metalloproteinases during the menstrual cycle in macaques is similar to that reported for women.…”
Section: Noncellular Componentsmentioning
confidence: 55%
“…IL-1-induced expression and release of MMPs is a crucial factor in the pathogenesis of rheumatoid arthritis (41), periodontal diseases (42), postmyocardial infarction remodeling (43), and in the remodeling of normal human endometrium (44). Furthermore, PTP␣ is important in cellular transformation (45).…”
Section: Discussionmentioning
confidence: 99%
“…In the endometrium, the control of MMP and TIMP production by ovarian steroids is locally mediated, at least partially, by cytokines secreted by the epithelial, stromal, inflammatory and endothelial cells of the endometrium [8][9][10][11][12][13]. IL-1 is produced by inflammatory cells, trophoblast and epithelial cells, and increases MMP-1, 3 and 9 production, while it inhibits TIMP-1 and 3 expression [14][15][16].…”
Section: Introductionmentioning
confidence: 99%